Relationship between digit ratio and learning style towards academic performance / Nurul Aiman Mohamed Shuhaimy - Mohamed Shuhaimy, Nurul Aiman (Faculty of Sport Science and Recreation, 2015)
Background: Digit ratio has been related to prenatal testosterone and fetal testosterone that has been shown to affect the areas in the brain that critical for memory and learning. Purpose: The purpose of this study was to determine the relationship between digit ratio and learning style towards academic performance. A total of 44 final year degree's students age from 22 to 25 years old were recruited to complete this study. The subjects are divided into two, low and the high digit ratio group. The Independent t-test used to measure the digit ratio and academic performance. The result from the study showed there were no significant differences in digit ratio and academic performance as the p>0.50. Next, from the result of One way ANOVA to investigate the relationship between learning style and academic performance showed that there is no significant difference between group and within the group on CGPA as the p>0.05 (p=0.87). The last analysis, which is Fisher Exact to determine the digit ratio and learning style also showed that there is no association between digit and learning style (p>1.00). As a conclusion, the result indicated that there is no significant relationship of the digit ratio and academic performance. Even though there is slightly showed that the low digit ratio has better achievement in their academic performance, still it's not enough to prove that low digit ratio as a main cause of a better academic performance.